Exploring the significance of Malaysian consumers' intentions to purchase green products / Zahoor Ur Rehman, Noor Aslinda Abu Seman and Amran Harun - Ur Rehman, Zahoor; Abu Seman, Noor Aslinda; Harun, Amran (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
The trend toward environmental sustainability is already gaining traction, and it is becoming more common in developed and developing countries. Consumers are becoming more aware of sustainability's importance and making more conscious choices about the products they purchase. The Malaysian Government is also promoting green technology by offering incentives and subsidies to companies producing eco-friendly products, also known as green products. Additionally, the Government is introducing regulations to reduce the carbon footprint of businesses and industries. On the other hand, the Government has signed the SDGs and is struggling to achieve them by 2030. Consumption and production are the primary focus of the 12th Sustainable Development Goal. A limited number of studies have been conducted to investigate the consumers' intentions toward purchasing green products in the Malaysian context, particularly on SDGs. Green products are available in the open markets in Malaysia, but consumers' behaviors and their intentions toward such products are considered low. This study is therefore conducted with the aim to investigate the level of consumers' intention towards purchasing green products. Using a 7-point Likert, 385 valid responses were collected from respondents in Selangor, Perak, and Johor. The study found that Malaysian consumers have a medium level of intentions when it comes to purchasing green products. This could be due to the fact that green products tend to be more expensive than their non-green counterparts, and many people are not willing to pay the extra cost. Also, there could be various factors influencing consumers' intentions to buy green products, which future studies can investigate.